1991
DOI: 10.1080/03601239109372740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal dietary hexachlorocyclohexane exposure on pup survival and growth in albino rats

Abstract: In adult albino rats, maternal dietary beta- and gamma-hexachlorocyclohexane (HCH) intake during gestation upto 400 ppm level did not affect the number of litters produced. But about 50 and 100% pup mortality was found in 200 and 400 ppm beta-HCH group within 5 days of birth. Maternal mortality was observed in 800 ppm beta-HCH group during third week of gestation. The effect of maternal dietary intake of HCH isomers at 50 and 250 ppm level during gestation and/or lactation on perinatal development was also stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Maternal mortality was observed in animals from the 40 mg/kg/day b-HCH dose group [43]. Concentrations of 0, 50, 200, 400, and 800 are equivalent to doses of 0, 2.5, 10, 20, and 40 mg/kg/day, assuming a default food consumption rate of 0.05 kg food/kg bw/day.…”
Section: Mammalian Oral Toxicity: Othermentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal mortality was observed in animals from the 40 mg/kg/day b-HCH dose group [43]. Concentrations of 0, 50, 200, 400, and 800 are equivalent to doses of 0, 2.5, 10, 20, and 40 mg/kg/day, assuming a default food consumption rate of 0.05 kg food/kg bw/day.…”
Section: Mammalian Oral Toxicity: Othermentioning
confidence: 99%
“…The LOAELs for liver effects are 5 mg/kg/day for a-HCH, 0.5 mg/kg/day for b-HCH, 5 mg/kg/day for g-HCH, and 5 mg/ kg/day for tech-HCH. In one study, Srinivasan et al found a NOAEL and LOAEL of 5 mg/kg/day and 10 mg/kg/day for b-HCH, respectively [43]. A beagle study conducted with g-HCH and lasting 104 weeks also seemed promising for TRV derivation; however, standard deviation values were not listed, and the number of animals dosed for the results pertaining to 50 weeks was not stated [34].…”
Section: Trvs For Mammalsmentioning
confidence: 99%
“…A dose of 20 mg lindane/kg body weight increased the incidence of fetuses with an extra rib in rats exposed during gestation days 6–15 and in rabbits exposed during gestation days 6–18 [24]. However, developmental anomalies or malformations were not observed in studies of mice exposed to 30 and 45 mg lindane/kg/day during gestation days 6–12 [20], in mice exposed to a single oral dose of 25 mg technical-grade hexachlorocyclohexane/kg [22]and in rats exposed during gestation to 25 and 50 mg technical-grade hexachlorocyclohexane/kg/day [25]. A recent study found that male mice exposed prenatally to 25 mg lindane/kg body weight during gestation days 9–16 exhibited postnatal changes in spermatogenesis that reversed with age [26].…”
Section: Introductionmentioning
confidence: 99%